KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN KELURAHAN TONDO KECAMATAN MANTIKULORE KOTA PALU - Yunika, Ulpa; Hattab, Syahruddin; Farista, Gita (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to find out the quality of population adminidtration services in tondo village, mantikulore district, palu city. The research method used is deskriptive qualitative. The data collection techniques used are observation, interviews and documentation.The location of this study coincides with the tondo village office, mantikulore district, palu city. The theory used in this study is the Zheithaml theory in Hardiansyah (2011:42) which consists of five aspects used in measuring service quality, the five aspects are Tangible, Reliability, Responsiveness, Assurance, and Emphaty. Based on the research results, it shows that the quality of population administration services in tondo village, mantikulore district, palu city is still not optimal. Because there are 2 (two) aspects that hinder the success of the quality of service in tondo village, namely the Tangible aspect which is still inadequate related to the lack of employee work space, computers, printers and waiting chairs, And the Assurance aspect is also considered not optimal because employees do not provide a guarantee of timely completion because there are often obstacles when carrying out the service process to the community such as the signatory is not in the office or the computer cannot be used. While the other 3 (three) aspects are Reliability, Responsiveness, and Emphaty have been running well.